Environmental risk assessment of concrete construction projects in developing countries based on Analytical Hierarchy Process method - Saman Solaimanian (Green Technologies and Sustainability, 2025)
Concrete construction, while essential for development, presents significant environmental challenges in developing countries. This study investigates the applicability of the Analytical Hierarchy Process (AHP) to prioritize environmental risks associated with concrete construction projects in these regions. By integrating expert judgment and stakeholder input through pairwise comparisons, the AHP analysis identified air pollution (39%), specifically dust generation, as the most critical risk, followed by water pollution (27.4%), resource depletion (12.5%), solid waste generation (16.3%), and habitat destruction (4.8%). Dust suppression emerged as the most effective mitigation strategy for air pollution. Water resource management, including rainwater harvesting, was crucial for minimizing water usage and contamination. Utilizing recycled or demolition waste was identified as key for reducing reliance on virgin resources and minimizing solid waste. This research demonstrates the effectiveness of AHP in prioritizing context-specific environmental risks for sustainable concrete construction in developing countries, providing a valuable framework for project managers and policymakers to address critical issues such as air and water quality and resource conservation.